2011
DOI: 10.1111/j.2041-1626.2011.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of single‐ and multi‐drug regimens in the management of classic (idiopathic) trigeminal neuralgia: an 11‐year experience at a single Sri Lankan institution

Abstract: The present study showed that the administration of multidrug regimens is a useful alternative in controlling trigeminal neuralgia in patients who are unable to tolerate higher doses of carbamazepine. Age, sex, ethnicity, and the side of affliction did not have a significant influence on the choice of drug regimen and the duration of treatment for pain control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…[ 63 64 65 ] Multi drugs are useful when patients are unable to tolerate higher doses of CBZ. [ 66 ] With an availability of increasing number of anticonvulsant drugs, it is likely that surgical option may not be offered for many years. [ 67 ]…”
Section: Medical Treatmentmentioning
confidence: 99%
“…[ 63 64 65 ] Multi drugs are useful when patients are unable to tolerate higher doses of CBZ. [ 66 ] With an availability of increasing number of anticonvulsant drugs, it is likely that surgical option may not be offered for many years. [ 67 ]…”
Section: Medical Treatmentmentioning
confidence: 99%
“…Carbamazepine was found to achieve good to excellent pain control in a majority of cases with TN, though statistical significance was not always reported 27,29‐31,35,49,68,70 . More recent studies showed reduction in pain as measured by VAS scores 5,69 . However, cohorts of patients with AFP and other facial neuralgias were largely unresponsive to carbamazepine 65,66 .…”
Section: Resultsmentioning
confidence: 99%
“…There were 24 therapies assessed. Carbamazepine was the most common intervention examined across studies, with 19 observational studies 5,6,[20][21][22][27][28][29][30][31]33,35,[65][66][67][68][69][70][71] and 9 randomized controlled trials, 23,44,[47][48][49]58,59,62,63 followed by botulinum toxin A with 11 observational studies 8,[12][13][14][15][16][17][18][19]41,72 32 oxcarbazepine, 7,36,44 pregabalin, 39 valproic acid, 38 gabapentin, 6,21,73 lamotrigine 21,60,62,64 ), local anesthetics (lidocaine, 37,53,57,61,67 tocainide 48 ), selective serotonin receptor agonists (sumatriptan…”
Section: General Study Interventions and Outcome Measuresmentioning
confidence: 99%
“…Other drugs, including oxcarbazepine [ 67 ], phenytoin [ 68 , 69 ], baclofen [ 70 , 71 ], lamotrigine [ 72 , 73 ], gabapentin [ 74 , 75 ], and sodium valproate [ 76 , 77 ], are also efficient in reducing the signs-symptoms of TN in most patients. Sometimes, some of the drugs are taken with carbamazepine as an adjuvant for the synergistic effects in relieving the TN symptoms [ 78 , 79 ]. The decreasing relief provided by carbamazepine or other drugs with continual use as well as unacceptable side effect profiles may necessitate the discontinuation of therapy.…”
Section: Trigeminal Neuralgiamentioning
confidence: 99%
“…In fact, it has been reported that approximately 50% of patients eventually require an operation to relieve pain [ 25 ]. Research has indicated that there is no significant influence of age, sex, ethnicity, or the side of the face on the decision of the medication regimen and the length of treatment for pain control [ 79 ].…”
Section: Trigeminal Neuralgiamentioning
confidence: 99%